INDUSTRIAL PRODUCTION'S ECOLOGIZING: DIRECTIONS, INSTRUMENTS - M.N. Ignatyeva; L.A. Mochalova (Экономика региона, 2008)
The industry of our country ensures the biggest part of GIP and at the same time exercises great influence on environment. The directions and instruments of Russian industrial production`s ecologizing which makes possible not only improvement of ecological situation but also going over to the sustainable development`s model are characterized by the article`s authors.